2016
DOI: 10.1039/c5cp05956a
|View full text |Cite
|
Sign up to set email alerts
|

How strong are the metallocene–metallocene interactions? Cases of ferrocene, ruthenocene, and osmocene

Abstract: An exhaustive exploration of the potential energy surfaces of ferrocene, ruthenocene and osmocene dimers has been performed. Our computations involving dispersion show that only four different isomers are present in each metallocene dimer. The collective action of small interaction energies of dispersive nature leads to a dissociation energy of 7.5 kcal mol(-1) for the ferrocene dimer. Dispersion has strong effects on the geometrical parameters, reducing the M···M distances by almost 1 Å. Our results also reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 51 publications
3
31
0
Order By: Relevance
“…Several algorithms to explore the potential/free energy surface coupled to an any electronic structure package have been successfully employed so far, such as AIRSS approach, [ 98 ] simulated annealing, [ 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ], kick methodology [ 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ], and genetic algorithms [ 9 , 21 , 33 , 112 , 116 , 117 , 118 , 119 ], among others.…”
Section: Theoretical Methods and Computational Detailsmentioning
confidence: 99%
“…Several algorithms to explore the potential/free energy surface coupled to an any electronic structure package have been successfully employed so far, such as AIRSS approach, [ 98 ] simulated annealing, [ 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ], kick methodology [ 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ], and genetic algorithms [ 9 , 21 , 33 , 112 , 116 , 117 , 118 , 119 ], among others.…”
Section: Theoretical Methods and Computational Detailsmentioning
confidence: 99%
“…Hence, the NCI approach often does not necessarily require a full DFT calculation 78 and has been successfully applied also to large-scale systems including porous crystalline materials, metal and guest-host complexes, OH-p interactions, and proteins. [78][79][80][81][82][83] Especially regarding repulsive interactions, we would like to point out that care must be taken when using a non-self-consistent density. In a promolecular density there is no Pauli-repulsion between the atomic densities to cause charge depletion.…”
Section: Density Descriptorsmentioning
confidence: 99%
“…Moreover, since previous work of Merino et al showed that stacking energies of Cp sandwich complexes of 3d, 4d and 5d metals are significantly different, 55 we have modified the metals in selected complexes by always using the metals of the same transition row. We have chosen 4d metals, since majority of indenyl complexes forming stacking interactions are with 4d metals (see Figure S2, Supporting Information).…”
Section: Potential Energy Surfaces Of Stacking Interactions Between Indenyl Ligandsmentioning
confidence: 99%